ДОСЛІДЖЕННЯ ЗДАТНОСТІ МЕЗЕНХІМАЛЬНИХ СТОВБУРОВИХ КЛІТИН ДО АНГІОГЕНЕЗУ IN VITRO ПІСЛЯ ЗБЕРІГАННІ У СКЛАДІ АЛЬГІНАТНИХ МІКРОСФЕР - Arakelian K., Hubenia О. (M.G. Kholodny Institute of Botany National Academy of Sciences of Ukraine, 2023)
Efficient preservation technologies required for endothelial cells is used in medicine and laboratory practice. Cell preservation at hypothermia may be more safe and beneficial for short-term storage. Herein, we have shown that Human Umbilical Vein Endothelial Cells (HUVEC) encapsulation into algi nate resulted in maintaining viability and angiogenesis possibility after encapsulation.
STUDY OF ENDOTHELIAL CELLS ANGIOGENESIS POSSIBILITY AFTER ENCAPSULATION INTO ALGINATE MICROBEADS.